Empagliflozin prevents neointima formation by impairing smooth muscle cell proliferation and accelerating endothelial regeneration - Dutzmann, Jochen; Bode, Lena Marie; Kalies, Katrin; Korte, Laura; Knöpp, Kai; Kloss, Frederik Julius; Sirisko, Mirja; Pilowski, Claudia; Koch, Susanne; Schenk, Heiko; Daniel, Jan-Marcus; Bauersachs, Johann; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Empagliflozin, an inhibitor of the sodium glucose co-transporter 2 (SGLT2) and developed as an anti-diabetic agent exerts additional beneficial effects on heart failure outcomes. However, the effect of empagliflozin on vascular cell function and vascular remodeling processes remains largely elusive. Methods/Results Immunocytochemistry and immunoblotting revealed SGLT2 to be expressed in human smooth muscle (SMC) and endothelial cells (EC) as well as in murine femoral arteries. In vitro, empagliflozin reduced serum-induced proliferation and migration of human diabetic and non-diabetic SMCs in a dose-dependent manner. In contrast, empagliflozin significantly increased the cell count and migration capacity of human diabetic ECs, but not of human non-diabetic ECs. In vivo, application of empagliflozin resulted in a reduced number of proliferating neointimal cells in response to femoral artery wire-injury in C57BL/6J mice and prevented neointima formation. Comparable effects were observed in a streptozocin-induced diabetic model of apolipoprotein E–/– mice. Conclusive to the in vitro-results, re-endothelialization was not significantly affected in C57BL/6 mice, but improved in diabetic mice after treatment with empagliflozin assessed by Evan’s Blue staining 3 days after electric denudation of the carotid artery. Ribonucleic acid (RNA) sequencing (RNA-seq) of human SMCs identified the vasoactive peptide apelin to be decisively regulated in response to empagliflozin treatment. Recombinant apelin mimicked the in vitro-effects of empagliflozin in ECs and SMCs. Conclusion Empagliflozin significantly reduces serum-induced proliferation and migration of SMCs in vitro and prevents neointima formation in vivo, while augmenting EC proliferation in vitro and re-endothelialization in vivo after vascular injury. These data document the functional impact of empagliflozin on vascular human SMCs and ECs and vascular remodeling in mice for the first time.